Impact of the War on German Firms: Energy Dependency and Price Increases - Jannis Bischof; Philipp Dörrenberg; Davud Rostam-Afschar; Thomas Simon; Johannes Voget (Wirtschaftsdienst)
Abstract The results of a continuous firm survey (conducted by the German Business Panel) are presented to shed light on the economic implications of the Russian invasion in Ukraine for German firms. The current developments impact the economic outlook and lead firms to invest and hire less. More than half of all surveyed firms report that gas rationing would affect their production either directly or indirectly through their supply chain. Furthermore, one-half of firms report that it would require less than one year to adjust to a hypothetical situation in which it has 50 % less gas. However, more than a quarter of firms indicate an adjustment period that is longer than two years. Price increases are a direct response to cost pressure that is caused by the development of energy prices and supply-chain disruptions.